PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN BALAI DESA PAKUURE SATU KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Monica C. Mongkau; Vicki R.B. Moniaga; Gene H.M. Kapantow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This study aims to determine the level of community participation in the construction of the Pakuure Satu village hall in Tenga District. This research was conducted in October to December 2018. The data used in this study were primary data and secondary data. Primary data is obtained from the field of research through direct interviews with respondents using a questionnaire. Secondary data was obtained from the Pakuure Satu Village government and agency documents related to research. The analysis used in this study is descriptive qualitative analysis techniques by explaining and using the Likert scale. The results of the study show that the level of participation of the Pakuure Satu community in the village hall development program at the planning, implementation and evaluation stages in the form of thoughts, skills, goods and money showed very much participation.Keywords: Community participation and Construction of Village halls